2021
DOI: 10.1111/1440-1703.12280
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of total fine root production using continuous inflow methods in tropical mangrove forest on Pohnpei Island, Micronesia: Fine root necromass accumulation is a substantial contributor to blue carbon stocks

Abstract: Fine root decomposition, mortality, and production are fundamental components of belowground carbon dynamics in mangrove ecosystems. Mangroves are highly productive ecosystems with huge carbon stocks; however, information on the dynamics of submerged fine roots in mangrove soils is limited. To estimate fine root production in several sites of mangrove communities on Pohnpei Island, Micronesia, we estimated continuous inflows using a simple mass balance model to combine ingrowth core and litterbag experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Although data on in-situ fine root production in deep mangrove soils (>30 cm) is scarce, Arnaud et al (2021) recently showed that a major fraction of fine root production occurs deeper than 30 cm. Other recent papers have also reported fine root production down to a depth of 50-60 cm below ground in mangrove forests (Fujimoto et al, 2021;Ono et al, 2022). Our visual inspection also revealed abundant live and dead fine roots in deep (> 50cm) soils.…”
Section: General Characteristics and Microscopic Observations Of Soil...supporting
confidence: 79%
“…Although data on in-situ fine root production in deep mangrove soils (>30 cm) is scarce, Arnaud et al (2021) recently showed that a major fraction of fine root production occurs deeper than 30 cm. Other recent papers have also reported fine root production down to a depth of 50-60 cm below ground in mangrove forests (Fujimoto et al, 2021;Ono et al, 2022). Our visual inspection also revealed abundant live and dead fine roots in deep (> 50cm) soils.…”
Section: General Characteristics and Microscopic Observations Of Soil...supporting
confidence: 79%
“…In the process of this succession, the tree density of Rhizophora species decrease gradually, while the B. gymnorrhiza trees increase gradually in the III(2)a stage, and the X. granatum trees are also mixed in the III(2)b stage. Ono et al (2021) revealed that Rhizophora species allocated more productivity to fine root production compared with other species on Pohnpei. Fujimoto et al (2021) showed that the fine root production of R. stylosa was higher than that of B. gymnorrhiza , which had approximately twice the trunk diameter.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated fine root production, which has a large effect on mangrove peat accumulation, using ingrowth core and litterbag methods (Ono et al, 2021). The study found that Rhizophora species produced more fine roots than other mangrove species when comparing the ratio of annual fine root production to the annual increase in aboveground biomass.…”
Section: Direction Of Future Researchmentioning
confidence: 99%
“…The Yaeyama Islands in Okinawa, in particular, are the northern limit of colonization by Rhizophora species. Rhizophora species are renowned for their remarkable capacity to sequester carbon due to their abundant production of very fine roots [47]. Nevertheless, there is a dearth of research concerning the variability of carbonate chemistry parameters (pCO2, TA, DIC) in mangrove waters within this region [40,48].…”
Section: Different Impact Of the Geomorphic Settings On Pco2 Dynamicsmentioning
confidence: 99%